Palliative care in the intensive care unit: fundamental aspects, ethical frameworks, and challenges in the Brazilian context - Brenno Cardoso Gomes; Anibal Basile Filho; Joao M. Silva (Frontiers in Medicine, 2026)
Significant medical advancements over the last century have reduced in-hospital mortality but raised concerns about prolonged hospitalizations and aggressive treatments potentially compromising the quality of life of critically ill patients. In Brazil, healthcare professionals often encounter ethical dilemmas and hesitancy when navigating orthothanasia and life-sustaining treatment decisions. This review examines the fundamental aspects of palliative care in the Intensive Care Unit (ICU), addressing the research question: What are the fundamental aspects of palliative care in the ICU? The study is positioned as a narrative review with systematic evidence collection, allowing for a multidimensional synthesis of clinical evidence, ethical frameworks, and regulatory challenges. The review focuses on four interrelated dimensions: (1) core clinical components (symptom management, communication, and decision-making); (2) ethical frameworks, specifically principalism and virtue ethics, guiding end-of-life decisions; (3) spiritual and existential care; and (4) contextual challenges in the Brazilian ICU setting, including barriers to life support limitation and strategies to prevent dysthanasia. Data were gathered from systematic searches in PubMed (MEDLINE), Scopus, LILACS, and the Virtual Health Library (VHL), spanning publications from 2004 to 2024, supplemented by legal resolutions and clinical guidelines. From 111 articles identified after deduplication, 36 were selected for full-text analysis following independent screening by two researchers. Key findings underscore the importance of structured communication, individualized symptom management protocols, and the role of virtue-based competencies in mitigating moral distress. Context-specific barriers in Brazil include legal uncertainty and training deficits. The reviewed evidence supports the implementation of structured goals-of-care conferences and interdisciplinary protocols to improve care quality and prevent dysthanasia.